2021
DOI: 10.1214/20-aop1478
|View full text |Cite
|
Sign up to set email alerts
|

The 2d-directed spanning forest converges to the Brownian web

Abstract: The two-dimensional directed spanning forest (DSF) introduced by Baccelli and Bordenave is a planar directed forest whose vertex set is given by a homogeneous Poisson point process N on R 2 . If the DSF has direction −e y , the ancestor h(u) of a vertex u ∈ N is the nearest Poisson point (in the L 2 distance) having strictly larger y-coordinate. This construction induces complex geometrical dependencies. In this paper we show that the collection of DSF paths, properly scaled, converges in distribution to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Given F n we have the information that the history region H n can not have a perturbed point in its interior and the explored region H n clearly depends on the past movements. At this place it is good to mention here that, as observed for the discrete DSF (defined on a random subset of Z d and studied in [RSS15]), or for the Poisson DSF (studied in [BB07], [CSST19]), it can be shown that the process {(g n (u 1 ),…”
Section: Markov Propertymentioning
confidence: 71%
See 1 more Smart Citation
“…Given F n we have the information that the history region H n can not have a perturbed point in its interior and the explored region H n clearly depends on the past movements. At this place it is good to mention here that, as observed for the discrete DSF (defined on a random subset of Z d and studied in [RSS15]), or for the Poisson DSF (studied in [BB07], [CSST19]), it can be shown that the process {(g n (u 1 ),…”
Section: Markov Propertymentioning
confidence: 71%
“…In [BB07] it has been shown that scaled paths of the successive ancestors in the DSF converges weakly to the Brownian motion and also conjectured that the scaling limit of the DSF on the Poisson points is the Brownian web. This conjecture remained open for long time and very recently it has been proved in [CSST19]. The scaling limit of the collection of all paths is much harder question as one has to deal with the dependencies between different paths also.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We are now prepared to prove (12). Indeed, since |i |≤M α N i = 0 if and only if A * n [M α ] = , we have…”
Section: Proposition 36 Let N ≥ 1 With Positive Probability the Aggre...mentioning
confidence: 98%
“…The above result is also one of the main ingredients to derive Lemma 4.4. The next one comes from [12] and provides finiteness (and also tail decay but we omit this part here) for the hitting time to 0 for a discrete-time, non-negative valued process {Y t : t ≥ 0} which is not necessarily Markov. Only supermartingale structure and moment conditions for increments are assumed.…”
Section: Proof Of Proposition 43mentioning
confidence: 99%
See 1 more Smart Citation